What Gender Theory Does Russian Social Psychology Need - Radina, N.K. (Socialʹnaâ Psihologiâ i Obŝestvo, 2024)
Objective. The article problematizes the theoretical field of gender studies and the concept of "gender", which are currently vulnerable in the socio-political context. The aim of the article is to determine the range of theories of Russian psychologists capable of solving topical issues in the field of gender social psychology outside of a politically conflicting discourse. Background. According to political theory, psychological knowledge can become a guide for political practice, this area of political science is called biopolitics. The constructivist theoretical field of gender studies belongs to the field of biopolitics; in Western gender theory, the deconstruction of gender is allowed not only as a social phenomenon, but also as a change in biological sex. Moreover, the possibility of deconstructing gender and sex is currently determined by political practice, not by psychological or psychiatric indications. The use of Western gender theory and the concept of "gender" in political conflicts pushes Russian social psychology to search for a theory based on the concepts of Russian psychologists focused on the analysis of the socio-psychological reality of gender relations. Results. The article emphasizes the impossibility of the reverse movement of science and the choice of the gender-role approach as outdated, not responding to the needs of modernity. Three theories are called productive and adequate to modern problems: the cultural-historical theory of L.S. Vygotsky, the subject-activity approach of S.L. Rubinstein, the theory of relations by V.N. Myasishchev. The concept of gender relations by I.S. Kletsina, one of the most popular modern concepts of gender in Russian psychology. Conclusions. Gender psychology is a new branch of social psychology, which turned out to be vulnerable to political initiatives in a period of socio-political instability. The search for new theoretical constructs and the educational activity of psychologists in the biopolitical field will help gender psychology overcome the crisis period. Цель. В статье проблематизируются теоретическое поле гендерных исследований и понятие «гендер», которые в настоящее время оказались уязвимыми в социально-политическом контексте. Цель статьи - определить круг теорий отечественных психологов, способных решать злободневные вопросы в области гендерной социальной психологии вне конфликтного с политической точки зрения дискурса.Контекст и актуальность. Согласно политической теории, психологическое знание может стать ориентиром для политической практики, эту область политологии называют биополитикой. Конструктивистское теоретическое поле гендерных исследований относится к полю биополитики, в западной гендерной теории допускается деконструкция гендера не только как социального феномена, но также - смена биологического пола. Более того, возможность деконструкции гендера и пола в настоящее время определяет политическая практика, а не психологические или психиатрические показания. Использование западной гендерной теории и понятия «гендер» в политических конфликтах подталкивает российскую социальную психологию к поиску теории, основанной на концепциях российских психологов, ориентированных на анализ социально-психологической реальности гендерных отношений. Результаты. В статье подчеркивается невозможность обратного движения науки, а выбор полоролевого подхода в исследованиях называется устаревшим, не отвечающим на запросы современности. В качестве продуктивных и адекватных современным проблемам называются три теории: культурно-историческая теория Л.С. Выготского, субъектно-деятельностный подход С.Л. Рубинштейна, теория отношений В.Н. Мясищева. Более подробно анализируется концепция гендерных отношений И.С. Клециной, одна из популярных современных концепций о гендере в российской психологии. Основные выводы. Гендерная психология - новая отрасль социальной психологии, оказавшаяся уязвимой перед политическими инициативами в период социально-политической нестабильности. Поиск новых теоретических конструктов и просветительская активность психологов в биополитическом поле помогут гендерной психологии преодолеть кризисный период.